2017
DOI: 10.1590/s0100-736x2017001100025
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy description of cervical region and hyoid apparatus in living giant anteaters Myrmecophaga tridactyla Linnaeus, 1758

Abstract: RESUMO.-[Descrição anatômica da região cervical e aparato hioide em espécimes vivos de tamanduá--bandeira, Mymercophaga tridactyla Linnaeus, 1758.] O Tamanduá-Bandeira possui adaptações anatômicas específicas, devido aos hábitos alimentares de ingestão de formigas e cupins. O arranjo singular do aparato hioide dos tamanduás é fundamental para a ingestão de alimentos. Sua descrição na literatura é baseada em peças e fósseis, o que dificulta a determinação de detalhes anatômicos existentes em animais vivos. As t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 13 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…The giant anteaters of this study presented the soft palate and the nasal and oral parts of the pharynx extended to the caudal level of the cervical region. These features were previously described in a study about cervical region and hyoid apparatus in living giant anteaters (Borges et al, 2017). The nasal and oral parts of the pharynx extended until the transition between the fifth and sixth cervical vertebrae, with the laryngeal part of the pharynx starting at this level (Borges et al, 2017).…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…The giant anteaters of this study presented the soft palate and the nasal and oral parts of the pharynx extended to the caudal level of the cervical region. These features were previously described in a study about cervical region and hyoid apparatus in living giant anteaters (Borges et al, 2017). The nasal and oral parts of the pharynx extended until the transition between the fifth and sixth cervical vertebrae, with the laryngeal part of the pharynx starting at this level (Borges et al, 2017).…”
Section: Discussionmentioning
confidence: 58%
“…This is more of an anatomical adaptation to accommodate the elongated tongue (Reiss, 1997;Naples, 1999;Borges et al, 2017). Borges et al, (2017) reported that it is important to know these anatomical details to avoid incorrectly identifying the nasal part of the pharynx as the cervical part of the trachea.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations